Empowering fisherwomen in Cilacap Village to improve family welfare with innovative fish-based Indonesian chili sauce products - Itsna Nurrahma Mildaeni; Dewi Susylowati; Alfalisyado Alfalisyado; Eko Muharudin (Community Empowerment, 2023)
Communities that depend on fishing for a living still live-in poverty and cannot prosper. In the midst of Indonesia's abundant maritime resources, the problem of fishermen's poverty is ironic. The seaside fishing community of Cilacap is one place that needs to raise its level of living. The use of training activities for fisherwomen is one possible strategy. The objectives of this activity are to: (1) boost fisherwomen's entrepreneurial motivation; (2) provide them with the knowledge and skills necessary to produce and package several varieties of fish-based chili sauce; and (3) educate them on how to market chili-based products. The following techniques are employed in this training: (1) introducing the program to partners; (2) training in the form of entrepreneurial motivation, skills in chili product innovation and product packaging, and promotion of chili products, (3) assistance, and (4) monitoring. The evaluation results showed an increase in post test scores. Based on the overall activities, the results were (1) increased entrepreneurial motivation of partners, (2) partners have the skills to produce and package various variants of fish-based chili sauce, and (3) partners have knowledge of promoting chili sauce products.